2017
DOI: 10.1002/2017jd027363
|View full text |Cite
|
Sign up to set email alerts
|

Optical power and energy radiated by return strokes in rocket‐triggered lightning

Abstract: The broadband optical radiation covering the visible and near‐infrared (VNIR) spectral regions (0.4–1.0 μm) has been measured from 70 negative return strokes (RS) in rocket‐triggered lightning; 17 events were recorded in 2011, and 53 were recorded in 2012. The radiometers were calibrated, and all measurements were time‐correlated with currents measured at the channel base. The risetime and peak of an irradiance waveform are determined primarily by the RS current and by the geometrical growth and total length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
6
17
0
Order By: Relevance
“…The 0.1‐μs value is in excellent agreement with experimental results by Carvalho et al (, ) and Quick and Krider () who found delays of 0.09 ± 0.05 and 0.09 ± 0.06 μs, respectively. Differently than Quick and Krider (), Carvalho et al () recorded luminosity from a 3‐m‐long channel segment near the ground. From such a short segment, the luminosity rise time is not masked by the geometrical growth of the return stroke in the field of view.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The 0.1‐μs value is in excellent agreement with experimental results by Carvalho et al (, ) and Quick and Krider () who found delays of 0.09 ± 0.05 and 0.09 ± 0.06 μs, respectively. Differently than Quick and Krider (), Carvalho et al () recorded luminosity from a 3‐m‐long channel segment near the ground. From such a short segment, the luminosity rise time is not masked by the geometrical growth of the return stroke in the field of view.…”
Section: Resultssupporting
confidence: 90%
“…Figure a shows the simulated temporal dynamics of visible power and electrical current in the channel, for conditions that resemble the aforementioned observations. The waveform is 0.5/50 μs with a 12‐kA peak current, similar to the median case in the data set (Quick & Krider, , Table 1). Figure b shows the first 3 μs of light emission, evidencing a 0.1‐μs delay between the rise of current and optical emissions in the channel.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Luminosity waveforms emitted by natural and rocket‐and‐wire triggered lightning processes such as return strokes and M‐components have been studied to determine how such optical radiation varies with time and channel height (e.g., Carvalho et al, , ; Carvalho, Uman, Jordan, Hill, et al, ; Jordan & Uman, ; Schonland, ; Wang et al, , , , ), to measure return stroke speeds in both time and frequency domains (e.g., Carvalho et al, ; Carvalho, Uman, Jordan, Hill, et al, ; Carvalho, Uman, Jordan, & Moore, ; Chen et al, ; Mach & Rust, ; Olsen et al, ; Schonland, ; Wang et al, , , , ) to determine how luminosity relates to the electric current flowing through the lightning channel‐bottom (e.g., Carvalho et al, , ; Idone & Orville, ; Qie et al, ; Wang et al, ; Zhou et al, ), to determine the optical energy radiated (e.g., Guo & Krider, , ; Krider, ; Krider et al, ), to examine the efficiency with which the discharge converts input energy to light (e.g., Connor, ; Krider et al, ), and to examine the lightning optical spectra, including deriving physical properties of the lightning channel such as temperature, electron density, and pressure from analyzing lightning spectra (e.g., Krider, ; Orville & Uman, ; Orville, , , , ; Prueitt, ; Quick & Krider, ; Uman, ; Uman et al, ; Walker, ; Walker & Christian, ).…”
Section: Introductionmentioning
confidence: 99%